Retail in Sicily: an Overall View - Girolamo Cusimano; Salvatore Cannizzaro; Maurizio Giannone; Donatella Privitera (Bollettino della Società Geografica Italiana)
In Sicily, the retail sector shows changes both from a structural point of view, with an increase in large-scale distribution at the expense of small businesses, and spatially, through the transfer of many commercial activities to the suburbs of cities or to extra-urban areas. This is a phenomenon that can also be observed in the rest of the country. The analysis of the most recent statistics in the sector, however, seems to highlight a significant flexibility of a part of the fabric of Sicilian commercial enterprises due to the widespread presence of small commercial businesses on the regional territory.